Depression and psychosocial correlates of liver transplant candidates: A systematic review. (8th August 2014) - Mohamed, Salina; Sabki, Zuraida Ahmad; Zainal, Nor Zuraida
Abstract Introduction Liver transplant candidates are vulnerable to develop depression. This paper aims to ascertain the prevalence of depression in liver transplant candidates and its psychosocial factors in a systematic review. Methods An extensive review via electronic databases (PubMed, EMBASE, CINAHL) and hand search were carried out to retrieve published articles up to December 15, 2013, using (Incidence OR Prevalence) AND Depress* AND liver transplant as the keywords. Information on the study design, patient characteristics, prevalence of depression, and its associated risk factors were extracted from included studies. Results There were 22 studies included in this review with a total of 3055 patients. The prevalence of depression in the liver transplant candidates ranges between 2% and 80%. Studies that used diagnostic tools found a narrower range of prevalence (4.5–43%) as compared to the self‐administered questionnaires (2–80%). Studies that used Beck Depression Inventory reported a higher prevalence than those studies which used Hospital Anxiety and Depression Scale (median = 28%, range = 2–80% versus median 17%, range 6.1–25.8%). A number of socio‐demographic factors, illness‐related and psychosocial factors were found to be associated with depression. Conclusion Prevalence of depression in liver transplant candidates is high, and early detection will improve survival and quality of life.